Penggunaan algoritma bubble sort pada Bahasa pemprograman java - ghifari, hayyi al (Maliki Interdisciplinary Journal, 2025)
The volume and complexity of data increases due to the rapid advancement of technology in this digital era, so that data management becomes increasingly difficult. So the use of sorting algorithms is one way to make data processing simpler. The Bubble Sort algorithm is a direct sorting technique discussed in this work. This algorithm compares and replaces elements in an array until no more swapping is needed, Bubble Sort is easy to understand and use, but it is not very efficient in half the time, especially when dealing with large data sets. However, this algorithm works very well with very small data sets or when the data is almost sorted. Practical uses of this algorithm include sorting student performance evaluations in mobile applications, which increases the efficiency of data processing. Analysis of the findings shows that Bubble Sort works best on a small scale, but other algorithms may work better on larger data sets.